2004
DOI: 10.1093/ajcn/79.6.946
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of satiation and satiety

Abstract: This review's objective is to give a critical summary of studies that focused on physiologic measures relating to subjectively rated appetite, actual food intake, or both. Biomarkers of satiation and satiety may be used as a tool for assessing the satiating efficiency of foods and for understanding the regulation of food intake and energy balance. We made a distinction between biomarkers of satiation or meal termination and those of meal initiation related to satiety and between markers in the brain [central n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
336
2
13

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(361 citation statements)
references
References 167 publications
10
336
2
13
Order By: Relevance
“…We found that within participant relations between responses of appetite scores and responses of hormones showed significant correlations with regards to PYY and insulin, but not CCK. Thus, our findings contribute to the debate about whether appetite hormones act as biomarkers of appetite (De Graaf et al, 2004;A. Flint et al, 2007;Lemmens et al, 2011) and support the notion of the subjective appetite measures being better correlates of energy intake than circulating levels of individually considered appetite hormones (Doucet et al, 2008).…”
Section: Hensd Placebosupporting
confidence: 81%
See 1 more Smart Citation
“…We found that within participant relations between responses of appetite scores and responses of hormones showed significant correlations with regards to PYY and insulin, but not CCK. Thus, our findings contribute to the debate about whether appetite hormones act as biomarkers of appetite (De Graaf et al, 2004;A. Flint et al, 2007;Lemmens et al, 2011) and support the notion of the subjective appetite measures being better correlates of energy intake than circulating levels of individually considered appetite hormones (Doucet et al, 2008).…”
Section: Hensd Placebosupporting
confidence: 81%
“…Even though the enhanced satiety and reduced hunger measured for 60 min (pre-breakfast period) after HENSD supplementation coincided with significantly higher plasma concentrations of PYY, CCK and insulin, during the pre-lunch period there was dissociation between appetite measures and expected action of hormonal appetite regulators, a phenomenon also found in some other studies (De Graaf, Blom, Smeets, Stafleu, & Hendriks, 2004;Doucet et al, 2008;Gielkens, Verkijk, Lam, Lamers, & Masclee, 1998). For further understanding of relations between responses of appetite scores and hormone responses we used a statistical approach that focuses on within participant relations between changes in appetite scores and changes in hormone concentrations (Lemmens et al, 2011) and obtained regression slopes and R 2 values for the regression of appetite scores on each of the measured appetite hormones.…”
Section: Hensd Placebosupporting
confidence: 71%
“…Several hormones, for example ghrelin, leptin and insulin, have been shown to be involved in the central regulation of appetite, hunger and satiation [11][12][13]. Receptors for these hormones have been found in the hypothalamus, and the involvement of these hormones in the energy homeostasis and food intake has widely been hypothesized [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It reduces appetite and increases energy expenditure by acting on the arcuate nucleus in the hypothalamus through its receptor (Ob-R) [10]. Circulating leptin levels correlate with fat mass in adults and children [11].…”
Section: Introductionmentioning
confidence: 99%